2021
DOI: 10.1016/j.jbc.2021.100296
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma-associated mutations in the DEAD-box RNA helicase DDX3X/DED1 cause specific defects in translation

Abstract: Medulloblastoma is the most common pediatric brain cancer, and sequencing studies identified frequent mutations in DDX3X , a DEAD-box RNA helicase primarily implicated in translation. Forty-two different sites were identified, suggesting that the functional effects of the mutations are complex. To investigate how these mutations are affecting DDX3X cellular function, we constructed a full set of equivalent mutant alleles in DED1 , the Saccharomyces cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…DDX3X has a well-described role as an activator of translation for mRNAs with long and structured 5′-UTRs (148). Consistent with this function, the growth defects seen across a large set of DDX3X mutants in yeast correlated best with defects in translation of structured 5′-UTR-containing mRNAs, rather than with global levels of translation (142). Although several studies have recently mapped the specific transcripts bound and regulated by DDX3X (146,147,149), which target genes are especially critical for suppressing or driving cancer remains unclear.…”
Section: Translation: Where Things Are Getting Madementioning
confidence: 75%
See 1 more Smart Citation
“…DDX3X has a well-described role as an activator of translation for mRNAs with long and structured 5′-UTRs (148). Consistent with this function, the growth defects seen across a large set of DDX3X mutants in yeast correlated best with defects in translation of structured 5′-UTR-containing mRNAs, rather than with global levels of translation (142). Although several studies have recently mapped the specific transcripts bound and regulated by DDX3X (146,147,149), which target genes are especially critical for suppressing or driving cancer remains unclear.…”
Section: Translation: Where Things Are Getting Madementioning
confidence: 75%
“…Genetic alterations in DDX3X consist of missense and loss-of-function mutations. Missense mutations occur mainly in the conserved helicase core (Supplemental Figure 2E), made up of two RecA-like domains that mediate ATPase and RNA-binding activity (141); and studies in both yeast and mammalian cells indicate that mutations associated with medulloblastoma are essentially loss-offunction alleles with impaired enzymatic activity (142)(143)(144)(145). Cellular effects of DDX3X mutants vary and likely depend on context, with globally impaired translation in some cases (146) and more transcript-specific impaired translation in other cases (147).…”
Section: Translation: Where Things Are Getting Madementioning
confidence: 99%
“…The percentage of various studies is shown in Figure 2. Meanwhile, the majority of studies, about 66% of studies, are dedicated to cell culture studies only (Baguet et al, 2007;Miyoshi et al, 2007;Arimoto et al, 2008;Eisinger-Mathason et al, 2008;Goulet et al, 2008;Busà et al, 2010;Gottschald et al, 2010;Guo et al, 2010;Kalra et al, 2010;Nikpour et al, 2011;Taniuchi et al, 2011aTaniuchi et al, ,b, 2014Park et al, 2012;Fournier et al, 2013;Pizzo et al, 2013;Thedieck et al, 2013;Chang et al, 2014;Kano et al, 2014;Podszywalow-Bartnicka et al, 2014;Yuan et al, 2014;Liu et al, 2015;Somasekharan et al, 2015;Szafron et al, 2015;Valentin-Vega et al, 2016;Weeks et al, 2016;Narayanan et al, 2017;Wall and Lewis, 2017;Takayama et al, 2018;Haghandish et al, 2019;Heberle et al, 2019;Kashiwagi et al, 2019;Mazloomian et al, 2019;Cui et al, 2020;Do et al, 2020;Brown et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To examine Ded1-dependent translational changes during oxidative stress, we utilized a set of previously published luciferase reporters with 5’UTRs derived from RPL41A that contain either a stem loop (ΔGfree = -3.7 kcal/mol) or are unstructured (Figure 7A) (24). The stem-loop containing reporter is translated less well than the unstructured one in wild-type cells, and this difference is often exacerbated in ded1 mutants (23, 24, 36). Here, we transformed these reporters into wild-type and ded1-ΔCT mutant cells, treated the cells with peroxide, and performed luciferase assays over a time course.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning assays for structured 5’UTR sequences were carried out similarly to (36). Briefly, cells transformed with either the control unstructured 5’UTR-firefly luciferase reporter (pFJZ342) or the stem-loop-containing 5’UTR-firefly luciferase reporter (pFJZ623) were cultured in triplicate in selective SD media at 30°C.…”
Section: Methodsmentioning
confidence: 99%